2014
DOI: 10.1002/wrna.1235
|View full text |Cite
|
Sign up to set email alerts
|

The role of SON in splicing, development, and disease

Abstract: SON is a nuclear protein involved in multiple cellular processes including transcription, pre-mRNA splicing and cell cycle regulation. Although SON was discovered 25 years ago, the importance of SON’s function was only realized recently when its roles in nuclear organization and pre-mRNA splicing as well as the influence of these activities in maintaining cellular health were unveiled. Furthermore, SON was implicated to have a key role in stem cells as well as during the onset of various diseases such as cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 58 publications
(241 reference statements)
1
30
0
4
Order By: Relevance
“…SON was shown to be a scaffold/structural nuclear speckle factor and its depletion leads to dispersion of splicing factors from nuclear speckles to the nucleoplasm 28, 29 . SON was also shown to regulate cell cycle progression, development, and disease 28, 29 . In control cells where SON is not depleted, we found that most of the M mRNA is in the cytoplasm at 6h post-infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SON was shown to be a scaffold/structural nuclear speckle factor and its depletion leads to dispersion of splicing factors from nuclear speckles to the nucleoplasm 28, 29 . SON was also shown to regulate cell cycle progression, development, and disease 28, 29 . In control cells where SON is not depleted, we found that most of the M mRNA is in the cytoplasm at 6h post-infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We then investigated whether NS1 and the cellular proteins involved in M1 mRNA localization and splicing at nuclear speckles physically interact with SON, a major player in nuclear speckle assembly and alternative splicing 28, 29 . The major form of the SON protein is ~263 kD and runs as a broad band in SDS- PAGE as it is likely post-translationally modified.…”
Section: Resultsmentioning
confidence: 99%
“…SON is a ubiquitously expressed and evolutionarily conserved gene in vertebrates and is located on the human chromosome region 21q22.11 [4]. It encodes the DNA-and RNA-binding protein SON, which functions in RNA splicing as well as gene repression [7][8][9][10][11][12][13]. A wide variety of genes are, thus, under the control of SON, and SON has been reported to be involved in cell cycle regulation and stem cell maintenance [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…SON is required for proper RNA splicing of selective genes (Ahn et al, 2011; Hickey et al, 2014; Lu et al, 2013; Lu et al, 2014; Martello, 2013; Sharma et al, 2011). Knockdown of SON leads to splicing defects in transcripts containing weak splice sites, and many of the affected genes are necessary for cell cycle progression and epigenetic modification (Ahn et al, 2011; Sharma et al, 2011).…”
Section: Introductionmentioning
confidence: 99%